Deletion of VDAC1 Hinders Recovery of Mitochondrial and Renal Functions After Acute Kidney Injury - Grazyna Nowak (Biomolecules, 2020)
Voltage-dependent anion channels (VDACs) constitute major transporters mediating bidirectional movement of solutes between cytoplasm and mitochondria. We aimed to determine if VDAC1 plays a role in recovery of mitochondrial and kidney functions after ischemia-induced acute kidney injury (AKI). Kidney function decreased after ischemia and recovered in wild-type (WT), but not in VDAC1-deficient mice. Mitochondrial maximum respiration, activities of respiratory complexes and FoF1-ATPase, and ATP content in renal cortex decreased after ischemia and recovered in WT mice. VDAC1 deletion reduced respiration and ATP content in non-injured kidneys. Further, VDAC1 deletion blocked return of activities of respiratory complexes and FoF1-ATPase, and recovery of respiration and ATP content after ischemia. Deletion of VDAC1 exacerbated ischemia-induced mitochondrial fission, but did not aggravate morphological damage to proximal tubules after ischemia. However, VDAC1 deficiency impaired recovery of kidney morphology and increased renal interstitial collagen accumulation. Thus, our data show a novel role for VDAC1 in regulating renal mitochondrial dynamics and recovery of mitochondrial function and ATP levels after AKI. We conclude that the presence of VDAC1 (1) stimulates capacity of renal mitochondria for respiration and ATP production, (2) reduces mitochondrial fission, (3) promotes recovery of mitochondrial function and dynamics, renal morphology, and kidney functions, and (4) increases survival after AKI.